Flouting Maxim Dalam Komedi “Lapor Pak” di Trans7 - Prapti Wigati Purwaningrum; Danang Dwi Harmoko (Wanastra: Jurnal Bahasa dan Sastra, 2022)
The purpose of this research is to explore several flouting of maxims, including maxims of quantity, maxim of quality, maxim of relevance spoken by the performers of the comedy "Lapor Pak" on Trans7 aired on November 11, 2021. This study uses a qualitative approach. Providing of data is done by using the method of observing and recording. The data is obtained in one episode with a guest star from the Governor of DKI Jakarta. The findings in this study are that of the eighteen maxim flouting, the most frequently occurring flouting are the Flouts exploiting maxim of quantity, the next is the Flouts exploiting maxim of quality, and the Flouts exploiting maxim of relation. The conclusion of this study is that when the Flouts exploiting maxim of quantity occurs in “Lapor Pak” performers, it tends to be done because the speaker wants to explain the answer in more detail. Next, the Flouts exploiting maxim of quality is done to avoid conflict and to show that the speaker does not like to talk about it. Meanwhile, the Flouts exploiting maxim of relation is carried out by the speaker because the speaker does not understand the meaning of the speech conveyed by the speech partner. In this case, it seems that the speaker accidentally Flouts exploiting maxim of relation. With the flouting of these maxims, the interaction that occurs between the speaker and the speech partner fails and immediately switches to another topic of conversation.Kata Kunci:Cooperative Principle, Flouting a maxim, Comedy « Lapor Pak »